Reproductive phenology of a northeast Brazilian mangrove community: Environmental and biotic constraints - Nadia, Tarcila de Lima; Morellato, Leonor Patrícia Cerdeira [UNESP]; Machado, Isabel Cristina (Elsevier Gmbh, Urban & Fischer Verlag, 2012)
Brazil has the third largest area of mangrove in the world, which is widely threatened by anthropogenic pressures. We carried out the first long-term phenological study investigating whether environment and competition for pollinators shape the reproduction of a western mangrove community in Brazil, and provide new information for mangrove conservation. We monitored monthly the flowering and fruiting of Avicennia schaueriana, Conocarpus erectus, Laguncularia racemosa and Rhizophora mangle, the only species composing this mangrove community. We applied circular statistics to detect seasonal trends, null models to test for aggregated, staggered or random flowering patterns, performed correlations between phenophases and climate, and calculated intra-specific phenological synchrony. Each species presented a different flowering pattern, from brief annual to continuous and from regular to irregular, resulting in a bimodal pattern at community level. Fruiting was annual or continuous and seasonally unimodal at community level. Precipitation showed the strongest correlation with reproduction for all species, except L. racemosa. Flowering was randomly distributed among species sharing pollinators and each species presented high intra-specific synchrony. The studied mangrove showed a diversity of flowering patterns despite the low number of species. Annual to sub-annual sequential flowering were prevalent, sustaining the pollinators of species all the year long, while the wind-pollinated species flowered continuously. We provide strong evidence that daylength, rainfall and temperature are driving the flowering and fruiting rhythm of these mangrove species. (c) 2012 Elsevier GmbH. All rights reserved.
Keywords: Avicennia schaueriana; Conocarpus erectus; Flowering and fruiting pattern; Laguncularia racemosa; Pollination; Rhizophora mangle